2006
DOI: 10.1254/jphs.scj05007x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Zacopride on Cisplatin-Induced Delayed Emesis in Ferrets

Abstract: Abstract. We evaluated the antiemetic effect of zacopride, a potent 5-HT 3 -receptor antagonist with 5-HT 4 -receptor agonist properties, on delayed emesis caused by cisplatin (5 mg / kg, i.p.) in ferrets, compared with granisetron, a selective 5-HT 3 -receptor antagonist. Multiple intravenous injections of zacopride at 1 mg / kg, a dose that completely inhibited acute emesis caused by cisplatin (10 mg / kg, i.v.), significantly reduced delayed emesis. Granisetron (3.2 mg / kg) also reduced delayed emesis but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We employed the 10 mg/kg and 5 mg/kg cisplatin models for acute and delayed emesis, respectively. 21,22) It has been reported that 5-HT 3 receptor antagonists completely abolish cisplatin-induced acute emesis, but only modestly inhibit the delayed emesis in experimental animal models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed the 10 mg/kg and 5 mg/kg cisplatin models for acute and delayed emesis, respectively. 21,22) It has been reported that 5-HT 3 receptor antagonists completely abolish cisplatin-induced acute emesis, but only modestly inhibit the delayed emesis in experimental animal models.…”
Section: Discussionmentioning
confidence: 99%
“…injected with cisplatin (5 mg/kg) at 08 : 30 h and their behavior was recorded with a video camera equipped with automatic night vision for 3 d. 22) During the experiments, ferrets were supplied with food (70 g/day) and water ad libitum. In prophylactic protocol experiments, FK886 (1.6 and 5 mg/kg, p.o.)…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Zacopride, as an activator of the I K1 , was found originally to be a potent 5‐HT 3 receptor antagonist (18) and 5‐HT 4 receptor agonist (19). Proper dosage of Zacopride was applied to gastrointestinal (GI) system as an antiemetic (20,21) or a GI prokinetic (22) agent. Zacopride could also act as an anxiolytic drug (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this may suggest that glucocorticoids exert their antiemetic action in the ferret via mechanisms not directly related to their known action to prevent eicosanoid synthesis. The anti-emetic action of the glucocorticoids could involve a suppression of other mediators involved at other points in the inflammatory cascade (6,20) or could be facilitated by other unknown mechanisms (3); such mechanisms may involve alterations in 5-HT function (38). Certainly, the number of genes directly activated by glucocorticoids is estimated to be between 10 and 100, with many genes being indirectly regulated through an interaction with other transcription factors and coactivators (39), meaning that future research on glucocorticoids may open new exciting possibilities for emesis control.…”
Section: Using Cox Inhibitors (21) and A Leukotriene Biosynthesis Inhmentioning
confidence: 99%